The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1038/npre.2010.4299.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of some cellular immune index in HIV infected participants

Abstract: The study was designed to evaluate some cellular immune index of HIV infected participants. For the study, 80 HIV infected participants were recruited for the study. They were aged 15 - 55 years. 45 of these participants were classified as Symptomatic HIV (Stage 11), while the remaining 35 were Asymptomatic HIV (Stage 1). Similarly, 40 HIV seronegative participants served as Control. Blood samples collected from the participants were used HIV screening and confirmation, CD4+ T cell count, absolute lymphocyte c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The results of this study suggest that plasma albumin level has the potential to be used as a surrogate prognostic marker for HIV-1 disease monitoring because of a signi icant increase in plasma albumin level at 12 months of therapy. This inding is supported by Ifeanyichukwu et al (2011);Sharma et al (2016) that low plasma albumin in HAART naive participants may be due to acutephase responses in HIV-1 infection leading to a wide range of pathophysiological reactions that resulted in increased levels of in lammatory biomarkers such as tumor necrosis factor (TNF) and interleukin-6 (IL-6), which are responsible for the reduction in hepatic albumin synthesis and increase in albumin leakage to the extravascular space while enhanc-ing the degradation of albumin. In a similar study by Ifeanyichukwu et al (2011), it was shown that HIV-1 infection is accompanied by a robust plasma pro-in lammatory and anti-in lammatory cytokine response in HAART naive individuals.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…The results of this study suggest that plasma albumin level has the potential to be used as a surrogate prognostic marker for HIV-1 disease monitoring because of a signi icant increase in plasma albumin level at 12 months of therapy. This inding is supported by Ifeanyichukwu et al (2011);Sharma et al (2016) that low plasma albumin in HAART naive participants may be due to acutephase responses in HIV-1 infection leading to a wide range of pathophysiological reactions that resulted in increased levels of in lammatory biomarkers such as tumor necrosis factor (TNF) and interleukin-6 (IL-6), which are responsible for the reduction in hepatic albumin synthesis and increase in albumin leakage to the extravascular space while enhanc-ing the degradation of albumin. In a similar study by Ifeanyichukwu et al (2011), it was shown that HIV-1 infection is accompanied by a robust plasma pro-in lammatory and anti-in lammatory cytokine response in HAART naive individuals.…”
Section: Discussionmentioning
confidence: 97%
“…This inding is supported by Ifeanyichukwu et al (2011);Sharma et al (2016) that low plasma albumin in HAART naive participants may be due to acutephase responses in HIV-1 infection leading to a wide range of pathophysiological reactions that resulted in increased levels of in lammatory biomarkers such as tumor necrosis factor (TNF) and interleukin-6 (IL-6), which are responsible for the reduction in hepatic albumin synthesis and increase in albumin leakage to the extravascular space while enhanc-ing the degradation of albumin. In a similar study by Ifeanyichukwu et al (2011), it was shown that HIV-1 infection is accompanied by a robust plasma pro-in lammatory and anti-in lammatory cytokine response in HAART naive individuals. The high proin lammatory cytokines were probably produced by monocytes and macrophages to initiate in lammation which is essential for the development of innate immunity, while the increased anti-in lammatory cytokines were stimulated probably to deactivate the activities of the pro-in lammatory cytokines.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations